Philosophy Course as a Process of Regeneration: A Hermeneutic Approach - Tasdelen, Vefa (KAMLA-RAJ ENTERPRISES, 2014)
Philosophical knowledge does not provide an objective characteristic unlike scientific knowledge. For this reason, its education and teaching should differ from other types of knowledge. Two problems accompany this differentiation: ( 1) Problem of teachability of philosophical knowledge and ( 2) problem of what kind of equivalence that this knowledge gets in the world of students even though it is taught. For questioning these two problems, the question What should be the goal of philosophy course can be the basis. The main objective of philosophy course in its simplest expression is to understand philosophy. This said research can be most suitably conducted within the framework of hermeneutic hypotheses, which is an art of understanding and interpreting. In this context, the expression that can best satisfy understanding is the concept of regeneration. Regeneration is an expression that can define the objective of philosophy education well. When the question Why philosophy education? is answered with to regenerate philosophy, this will be an answer suitable to the nature of philosophy and philosophy education.
Keywords: Philosophy; Philosophy Course; Hermeneutics; Understanding; Education; Regeneration; Anthropology; Science & Technology - Other Topics; Social Sciences - Other Topics